Систематизація параметрів процесу очищення анілоксового валу - Канєвський, Б. М.; Зоренко, Я. В. (ТОВ «Видавництво Ліра-К», 2025)
The work considered the parameters of the process of contamination and cleaning of the anilox roller in flexographic printing. The result of the work was the development of a systematization of the parameters influencing the process of cleaning the anilox roller.
Keywords: очищення анілоксового валу; flexographic printing